Determination of the Contract Risk Buffer in the Construction Industry - Więcław-Bator, Lidia Elżbieta; Kruszka, Leopold (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents an analysis of the volatility of construction project implementation costs, with a particular focus on medium- and long-term projects. Inherent fluctuations in the prices of construction inputs require contractors to use advanced methods of calculating bid prices and formulating base budgets, in accordance with best practices in cost risk management. The article presents an algorithm for determining the contract risk buffer resulting from the increase in the cost of construction work, taking into account the key determinants of risk and their impact on final investment costs.
Keywords: construction costs; risk buffer; heterogeneity of construction processes; construction economics